THE EFFECT OF FOREIGN DEBT, FOREIGN DIRECT INVESTMENT, EXPORTS, AND IMPORTS ON ECONOMIC GROWTH IN ASEAN-5 COUNTRIES IN 2000 – 2017 (BEFORE AND AFTER THE GREAT RECESSION OF 2008) - Alhazimi, Rakka; Supriyono, Supriyono (Journal of Applied Economics in Developing Countries, 2020)
The economic growth rates of developing countries in the ASEAN region such as Indonesia, the Philippines, Laos, Myanmar and Vietnam are currently not high enough to immediately align with the economies of developed countries. This is evidenced by the gross domestic product (GDP) per capita of developing countries in ASEAN which is still far from the GDP per capita of developed countries, so ASEAN developing countries need additional development capital in the form of foreign debt and foreign direct investment (FDI) and conduct international trade in the form of exports and imports. This study aims to determine the effect of foreign debt, FDI, exports and imports on economic growth in ASEAN countries. This study uses a quantitative approach. The data used are secondary data in the form of panel data from Indonesia, Philippines, Laos, Myanmar and Vietnam in 2000 - 2017. Data analysis methods used are panel data regression with fixed effect models (weighting cross-sections seemingly unrelated regression). The results showed that the variables of foreign debt, FDI, exports and imports had a positive and significant influence on economic growth. Conversely, the export variable has a negative influence on economic growth. The results of time series analysis show that the variables of foreign debt, FDI, exports, and imports have a significant effect on economic growth in the period before the recession in 2008. In the period after the 2008 recession, the variables of foreign debt, exports and imports have a significant effect on economic growth, but the variable of FDI have no significant effect on economic growth.Keywords: Economic Growth, Foreign Debt, FDI, Export, Import